2016
DOI: 10.4265/bio.21.135
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Laboratory Study to Validate New Rapid Screening Methods for <i><i>Kudoa septempunctata</i></i>

Abstract: Kudoa septempunctata is the causative agent of a food-borne disease associated with the ingestion of raw olive flounder. As the current qRT-PCR method for its detection is timeconsuming, a rapid and simple method is required. Recently, a new real-time loop-mediated isothermal amplification LAMP method and an immunochromatography method, whose sensitivities are intended to be compatible with that designated in the official analytical method 10 5 spores/g olive flounder , have been developed. To validate these n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Development of field‐based molecular tools, in the form of rapid diagnostic tests, that offer the same specificity and sensitivity as laboratory‐based diagnostics, would be of use in this regard (Ohnishi et al., 2016). Lateral‐flow immunochromatography, in particular, holds promise for more rapid screening of fish fillets at seafood processing factories.…”
Section: Advancing Marine Ecosystem Forecasting: Enhancing the Biological Dimensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Development of field‐based molecular tools, in the form of rapid diagnostic tests, that offer the same specificity and sensitivity as laboratory‐based diagnostics, would be of use in this regard (Ohnishi et al., 2016). Lateral‐flow immunochromatography, in particular, holds promise for more rapid screening of fish fillets at seafood processing factories.…”
Section: Advancing Marine Ecosystem Forecasting: Enhancing the Biological Dimensionmentioning
confidence: 99%
“…Lateral‐flow immunochromatography, in particular, holds promise for more rapid screening of fish fillets at seafood processing factories. Innovations such as real‐time loop‐mediated isothermal amplification methods and immunochromatography can vastly improve the efficiency of collecting biological data on parasitic infection (Ohnishi et al., 2016) and harmful marine biotoxins (McPartlin et al., 2016) in the factory, and results of these tests can be then integrated into marine ecosystem forecasts.…”
Section: Advancing Marine Ecosystem Forecasting: Enhancing the Biological Dimensionmentioning
confidence: 99%
“…K. septempunctata has recently been linked to human food poisoning cases in Japan [15]. K. septempunctata spores have been isolated from raw olive flounder within 20 h after the fish was consumed by patients who developed diarrhoea, and the patients recovered completely within 24 h, suggesting that K. septempunctata spores are associated with transient clinical symptoms [10].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported clinical symptoms in animal models including the mouse [1, 7, 10], and permeability increase in the human intestinal epithelial monolayer [14]. Few reports on detection methods for K. septempunctata are available [10, 15, 16]. Contaminated fish occasionally reach the consumer through raw olive flounder fillets as infection is not tested for prior to consumption.…”
Section: Introductionmentioning
confidence: 99%